Cote d'Ivoire : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Cote d'lvoire during 1990-95. In 1994, the resumption of growth, initially concentrated in the area of some traded goods, became more widespread during the second half of 1994, offsetting the devaluation-induced contraction in the nontraded goods sectors and in the sectors sheltered from competition, which both suffered from the reduction in real disposable income. Output in volume terms increased at a rate of 4.5 percent in the primary and secondary sectors, and contracted further in the tertiary sectors.